APAKAH KINERJA KEUANGAN DAERAH MENGGAMBARKAN KEMISKINAN DI JAWA TIMUR - Norsain Norsain; Mohammad Rofik (STIE Mahardhika, 2022)
This study is to examine the financial performance of district / city governments affecting poverty in East Java. The data used in this study is research data, which is a combination of time series data with cross section data with a research sample of 38 districts/ cities for six years of observation from 2013 to 2018. Fixed Effect Model (FEM) as the chosen model. Variable X1, the degree of decentralization has an effect on variable Y. These results indicate that the degree of decentralization has a significant negative effect on poverty. Variable X2 regional financial dependence has a positive effect on variable Y poverty. Variable X3 regional financial independence has no effect on variable Y poverty. Variable X4 PAD effectiveness does not affect variable Y poverty. Variable X5 PAD efficiency has no effect on variable Y poverty. Simultaneously the variable degree of decentralization, regional financial dependence, regional financial independence, effectiveness and efficiency has a significant effect on the poverty variable. R-squared is 0.985112, that variable Y poverty is explained by variable X regional financial performance of 98.51%. While the remaining 1.49% is explained by other factors that are not included in the model